Nursing care for rheumatoid arthritis patients with the application of rheumatic gymnastics for pain management: A case study - Putri, Amelia (Science Center Group, 2024)
Background: Rheumatoid arthritis is a chronic inflammatory autoimmune disease that causes persistent joint pain, stiffness, and functional impairment. Chronic pain in rheumatoid arthritis often reduces mobility, interferes with daily activities, and decreases quality of life. Non-pharmacological interventions such as therapeutic exercise are increasingly recommended to complement pharmacological treatment in managing pain and improving joint function. Objective: This study aimed to evaluate nursing care for rheumatoid arthritis patients through the application of rheumatic gymnastics as a non-pharmacological intervention for pain management. Methods: This study employed a descriptive case study design using a nursing care approach. The study was conducted in a primary healthcare center involving a patient diagnosed with rheumatoid arthritis who experienced chronic joint pain. The intervention consisted of rheumatic gymnastics performed three times per week for four weeks, with each session lasting approximately 30 minutes and including warm-up, core exercise, and cooling-down phases. Pain intensity was measured using the Numeric Rating Scale (NRS) before and after the intervention. Data were analyzed using descriptive analysis to evaluate changes in pain intensity following the intervention. Results: The patient initially reported severe pain with an NRS score of 7 before the intervention. After four weeks of rheumatic gymnastics, the pain intensity decreased to an NRS score of 3, indicating mild pain. The patient also reported improved joint mobility and increased confidence in performing daily activities. The intervention demonstrated positive outcomes in both physical comfort and psychological adaptation. Conclusion: Rheumatic gymnastics integrated into nursing care may serve as an effective non-pharmacological strategy for reducing pain intensity and improving functional ability in patients with rheumatoid arthritis. The intervention can be implemented in primary healthcare settings to support holistic pain management.